Pengembangan E-Modul Interaktif Berbasis Augmented Reality pada Materi Ikatan Kimia - Indah Putri Wulandari; Ayi Darmana (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
The low learning outcomes of students in chemistry subjects are due to the limitations of teaching materials that are interesting, interactive, and applicable to technological developments. Learning is still dominated by the use of package books, while teachers have not fully utilized digital-based media in the learning process. This condition has an impact on students' low interest and understanding of concepts, especially in abstract chemical bonding materials. This research aims to develop and determine the feasibility level of Augmented Reality-based interactive e-modules as innovative teaching materials in chemistry learning. The research method used is Research and Development (R&D) with the ADDIE development model. The subjects of this research consist of one lecturer who is a material expert and one lecturer who is a media expert, while the object of the research is an interactive e-module based on Augmented Reality on chemical bonding materials. The research instruments used were non-test instruments, namely needs analysis questionnaires, interview sheets, and feasibility questionnaires for material experts and media experts. The results of the analysis showed that the feasibility level of Augmented Reality-based interactive e-modules reached 96.6% from material experts and 92.9% from media experts, with an average feasibility of 94.75% which was included in the very feasible category. Thus, the e-modules developed can be used as an alternative to more modern teaching materials, because they are able to visualize abstract concepts of chemical bonds through 3D elements based on Augmented Reality, so that it has the potential to improve the quality of learning and student understanding.